Comparison of the Effects of Body Acupressure and Ear Acupressure on Shoulder Pain in Iranian Patients Undergoing Laparoscopic Cholecystectomy: A Randomized Controlled Trial - Mona Sadat Zohourparvaz; Hamidreza Bahrami Taghanaki; Mohammadreza Ghasemian Moghadam; Seyyed Abolfazl Vagharseyyedin (Tehran University of Medical Sciences, 2023)
Shoulder pain after laparoscopic cholecystectomy surgery is one of the important complications that can increase patients' discomfort and their length of stay at the hospital. This study aimed to compare the effects of body acupressure and ear acupressure on shoulder pain in patients undergoing laparoscopic cholecystectomy. 101 patients participated in this randomized controlled clinical trial in 2022. They completed the demographic information form and the Spielberger State-Trait Anxiety Inventory. Then, they were assigned into ear acupressure, body acupressure, and control groups through block randomization. The control group did not receive any intervention. The amount of shoulder pain in patients was recorded in all three groups by using the VAS one (T1), four (T2), and eight (T3) hours after the intervention. Data analysis was done with the SPSS software (v. 25). The mean shoulder pain score in the ear acupressure group was lower than that in the body acupressure group and the control group in T1 (P<0.001). The median shoulder pain score in the body acupressure group was lower than that in the control group at T2 (P<0.001); the median pain score in the ear acupressure group was significantly lower than that in the other two groups at T2 (P<0.001). The median pain score in the control group was higher than that in the body acupressure and ear acupressure groups at T3 (P<0.001). We observed no statistically significant difference between the body acupressure and ear acupressure groups at T3 (P= 0.12). Statistical analysis showed no difference between the mean anxiety scores of patients in the control, body acupressure, and ear acupressure groups (Z=1.41, P=0.49). Body acupressure and ear acupressure were effective in reducing shoulder pain after laparoscopic cholecystectomy, but ear acupressure was more effective and it showed its analgesic effect faster than body acupressure.